Analisis Kemampuan Spasial Pada Bangun Ruang Sisi Datar Ditinjau Dari Perbedaan Gender - Purborini, Sefriana Dyah; Hastari, Ratri Candra (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2018)
Spatial ability is important in studying the solid geometry. A person who has good spatial skills will easily imagine objects in three dimensions. Factors that influence the different strength of students one of which is the gender difference. This study aims to analyze students' spatial skills judging from the student gender differences. This research is descriptive qualitative that is collecting data in the form of description or sentence. The approach of this research is a qualitative approach. Research subjects in this study consisted of 4 students of class VIII C SMP Negeri 2 Trenggalek. The technique of collecting data of this research is observation, test, and interview. Test results and interviews are analyzed based on the spatial ability, they are the ability of imagination, conceptualization, problem-solving, and pattern searching. The results showed that: male students (1) able to solve the problem using the help of images and illustrate the solution; (2) able to connect data that is known to the concept possessed; (3) able to see problems from different angles; and (4) able to find patterns in solving problems. While female students showed: (1) able to solve the problem using the help of images; (2) able to mention known concepts.Key Word: Gender, Polyhedron, Spatial Ability